Akibat Hukum Akta Jual Beli dengan Objek Kapal yang dibuat Sebagai Perjanjian Simulasi (Analisis Putusan Pengadilan Negeri Samarinda Nomor 42/Pdt.G/2024/PN.Smr) - Anggraini, Sabrina Dwi; Putra, Mohamad Fajri Mekka (Universitas Batanghari Jambi, 2025)
The sales agreement between the seller and the buyer occurs at the moment there is a meeting of the minds and a declaration between them regarding the goods and the price. However, the transfer of ownership of the goods being sold does not necessarily occur simultaneously with the agreement reached between the parties. The deed made by the Notary serves as evidence to guarantee the truth of the transaction in carrying out a legal act, in this case, a sale and purchase. However, in practice, unlawful acts are still found to be committed by the parties in making an agreement, such as a simulated agreement. Therefore, this research aims to understand the legal consequences of buying and selling ships that are made as simulated agreements and to analyze the regulations regarding the Sale and Purchase Deed with ship objects. The research method used in this study is a qualitative type with a descriptive-analytical nature, utilizing primary legal materials and secondary legal materials. The results and discussion of this research are the regulations regarding the ship sale and purchase deed, where the evidence of the transfer of ownership of the ship is in the form of a ship sale and purchase deed made in the presence of a notary (Article 18 paragraph (3) letter a of the Minister of Transportation Regulation on Ship Registration). Meanwhile, the legal consequence is that the party who feels aggrieved by the simulated agreement does not receive legal protection from the creation of the simulated agreement, and the aggrieved party cannot claim compensation.